Morphological, physiological features and differences of Vriesea splendens ’Fire’ plants during in vitro multiplication and rooting - Ördögh, M. (International Journal of Horticultural Science, 2022)
During in vitro multiplication and rooting of Vriesea splendens ’Fire’, 0.1, 0.2, 0.4 and 0.8 mg l-1 benzyladenine (BAP), benzyladenine-riboside (BAPR), kinetin (KIN), meta-topoline (MT), indole-butyric acid (IBA) and naphthalene-acetic acid (NAA) were added to basal Murashige and Skoog (1962) MS medium. As compared to the hormone-free control, plants developed significantly more shoots on medium supplemented with almost all cytokinins (excepting KIN), especially BAP resulted the highest multiplication up to almost 26 shoots. Enhancement of cytokinin concentrations increased shoot number (and in case of BAP, peroxidase activity) but decreased plant height and rooting parameters. Regarding root production, both auxins were definitely beneficial (0.2 mg l-1 NAA resulted more than 7.5 roots and higher auxin concentrations efficiently stimulate root elongation); however, KIN had similar effects. After a three-month duration time of acclimatization, we observed that plants which were previously cultured on medium containing certain cytokinins (KIN in all doses and 0.1 mg l-1 MT) or both auxins had greater survival, moreover, as negative after-effect, higher cytokinin concentrations reduced the number of survived specimens.